PERTUNJUKAN TOPENG BONDRES SEBAGAI MEDIA PENDIDIKAN AGAMA HINDU - Ni Wayan Yuniastuti; Ni Luh Putu Trisdyani; Ida Bagus Putu Eka Suadnyana (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2020)
Art in the Hindu perspective has a very basic position, because Hindu religious life cannot be separated from the elements of art. Basically, any form of art is the result of an artist's creativity, as a result of the artist's taste, creativity and initiative, which cannot be separated from the bonds of noble cultural values, including aesthetics. Performing arts are a powerful means of educating people's attitudes, mentality, and morals. This is possible because a performance such as the Bondres Mask is a form of communication and always has messages delivered. In connection with the above problem, then the idea arose to study the performance of the mask art so that it knows the process of Bondres Mask as a Hindu Religious Education Media. In addition, it is also to find out the function of the role of Bondres Mask as a Hindu Religious Education Media. In this scientific work the writer will reveal the existence of Bondres Mask as a spectacle and guide, although lately there have been lifted mask dances (Atmaja 2004), (Sueka, 2006), and (Kodi, 2006), but the studies are different.Keyword: Performance, Bondres Mask, Religious Education Media